Effect of Early versus Delayed Cord Clamping on Hematological Parameters of Term Neonates: Pengaruh Penjepitan Tali Pusat Dini Dibandingkan dengan Tertunda pada Parameter Hematologi Neonatus Aterm - Chaithra Ravishankar; Ratan Kumar Das; Chandra Bhanu Dalal; Tapan Pattanaik (Indonesian Journal of Obstetrics and Gynecology, 2022)
Objectives : To compare the serum bilirubin, hemoglobin, and hematocrit in term infants undergoing delayed cord clamping with early cord clamping after normal and caesarean delivery.Methods : This is a prospective observational study. The neonates in which cord clamping was done within 15 seconds were considered in early cord clamping (ECC) group and where cord clamping was done after 1 minute was considered in delayed cord clamping (DCC) group. The PCV, Hb, serum bilirubin were observed after 48 hours in both the groups and compared.Results : There was statistically significant difference in means of Hb level (p = 0.001) and PCV level (p = 0.001) between DCC and ECC group whereas no statistically significant difference was present in total serum bilirubin level (p = 0.359).Conclusion: There was no significant increase in risk of polycythaemia and hyperbilirubinemia between delayed cord clamping and early cord clamping group rather has beneficial effects in increasing the haemoglobin and haematocrit in the infants.Keywords : delayed cord clamping, early cord clamping, hematocrit, hemoglobin, serum bilirubin, hyperbilirubinemia. Abstrak Tujuan: Untuk membandingkan bilirubin serum, hemoglobin, dan hematoklit pada bayi aterm yang dilakukan delayed cord clamping dan early cord clamping setelah persalinan normal dan seksio sesarea.Metode: Studi ini merupakan studi prospektif. Neonatus yang dilakukan cord clamping dalam 15 detik dikelompokkan pada delayed cord clamping (DCC). PCV, Hb, bilirubin serum diobservasi dalam 48 jam pada kedua kelompok, kemudian dibandingkan.Hasil: Terdapat perbedaan signifikan antara kadar Hb (p = 0,001) dan PCV (p = 0,0010 antara kelompok DCC dan ECC, sedangkan tidak terdapat perbedaan signifikan pada kadar bilirubin serum total (p = 0,3590Kesimpulan: Tidak terdapat peningkatan signifikan polisitemia dan hyperbilirubinemia antara DCC dan ECC.Kata kunci: delayed cord clamping, early cord clapming, hematokrit, hemoglobin, serum bilirubin, hyperbilirubinemia